Electronic Information Technologies in Life Science: Assessments of The State and Health Benefits of Garden and Park Plantings: Life Sciences-Medicine - Imanbayeva, A. A.; Belozerov, I. F.; Gassanova, G.G.; Syrlybekkyzy, S.; Ondassynova, A. S. (International Journal of Life Science and Pharma Research, 2022)
As a substantial part of urban parks and green spaces, plant landscapes can favor people’s physical health by raising surrounding negative air ions and oxygen released, and also decreasing harmful particulate matters and noises. In the prevailing era, the description of the special computer program "PLANT-EST-KZ" developed in the MEBG is given, the database of which currently includes the most complete information about 94 green devices of residential and industrial zones of 5 settlements of the Mangystau region of 13 districts. The aim of the study is mainly intends to analyze the role of electronic information technologies in life science, especially the assessments of the state and health benefits of garden and park plantings. Over the course of this study, a comprehensive scale for assessing the health benefits and aesthetics of green devices, which takes into account 37 structural, commemorative, ecological, biological, chemical and agrotechnical characteristics of garden and park objects, is considered in relation to the arid conditions of Mangystau. A comparative analysis of the health benefits and aesthetics of green devices for various functional purposes is given. Based on the results obtained, it is necessary to activate the implementation of the assortment of wood lianas (4.3%), varietal roses (18.4%) and flower and ornamental plants (14.9%) in the coming years. The improvement and implementation of the "PLANT-EST-KZ" program in the practice of green construction will grow to be the foundation for a proper evaluation of the decorative nature of Mangystau landscaping and the development of efficient means for the reconstruction of existing and creation of new garden and Park plantations.